Translation Procedures Applied in Localized Websites - Aryadi Jaya, I Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 26 No 2 (2019): September, 2019)
Many companies have their website contents translated into languages spoken by many people globally. Here, translation plays an important role in making people who speak different languages know and understand more about certain products, services, terms and conditions, and also as a part of sales and marketing strategies.           The data in the form of sentences containing terminologies in SL (English) and their translations in TL (Indonesian) were collected from Booking.com and Expedia.co.id using the observation method and the note-taking technique. The results showed that the types of terminologies analyzed in this study based on the data sources are: 1) power words; 2) hospitality terms; 3) Internet terms; and 4) legal terms. The translation procedures used in translating the selected terminologies vary greatly, namely transference, literal, naturalization, synonymy, couplet, shift, componential analysis, reduction, and expansion.  Keywords : terminologies, localization, booking websites